2020
DOI: 10.1101/2020.02.12.946558
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Induced copy-back RNA synthesis as a novel therapeutic mechanism against RNA viruses

Abstract: The viral RNA-dependent RNA polymerase (RdRp) is a well-established target for development of broad-spectrum antiviral therapeutics. Incorporation of ribonucleotide analogues by the RdRp will either cause termination of RNA synthesis or mutagenesis of the RNA product. We demonstrated recently that incorporation of a pyrazinecarboxamide ribonucleotide into nascent RNA leads to pausing and backtracking of the elongating RdRp. Here, we provide evidence for the single-stranded RNA product of backtracking serving a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…While the evidence highlights a role for in trans template-switching events, it remains unclear as to whether in cis events are also driving the evolution of viruses with imprecise genomes. Ongoing studies investigating the behaviour of polymerases during RNA synthesis suggests that both in trans template-switching, and in cis copy-back type recombination events can occur [ 39 , 40 ], and such research may offer valuable insights into our further understanding of this fundamental process.…”
Section: Discussionmentioning
confidence: 99%
“…While the evidence highlights a role for in trans template-switching events, it remains unclear as to whether in cis events are also driving the evolution of viruses with imprecise genomes. Ongoing studies investigating the behaviour of polymerases during RNA synthesis suggests that both in trans template-switching, and in cis copy-back type recombination events can occur [ 39 , 40 ], and such research may offer valuable insights into our further understanding of this fundamental process.…”
Section: Discussionmentioning
confidence: 99%
“…One of these antivirals is Favipiravir (FPV), that directly inhibits viral replication and transcription by selective inhibition of the viral enzyme RNA-dependent RNA polymerase (RdRP) (37,38). FPV is a ribonucleotide analogue (fluorinated base analogue with a pyrazine carboxamide) (39). Studies of the nucleotide addition to the elongation complex of the viral RdRP showed that FPV is capable to make RdRP pause during the reading process, which leads to backtracking (an attempt to recover reading errors), that when repetitive, causes the enzyme to interpret them as a prematurely terminated product, thus stopping the elongation and therefore interrupting the viral replication process (40).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that an effective treatment for COVID-19 severe patients should combine a modulator of the immune response with a direct antiviral drug against SARS-CoV-2, in order to address both the hyperin ammatory effects of the immune dysregulation and the viral load, thus yielding best results. Favipiravir (FPV), directly inhibits viral replication and transcription by selective inhibition of the viral enzyme RNA-dependent RNA polymerase (RdRP) (41)(42)(43)(44).…”
Section: Introductionmentioning
confidence: 99%
“…One of these antivirals is Favipiravir (FPV), that directly inhibits viral replication and transcription by selective inhibition of the viral enzyme RNA-dependent RNA polymerase (RdRP)(37,38). FPV is a ribonucleotide analogue (fluorinated base analogue with a pyrazine carboxamide)(39). Studies of the nucleotide addition to the elongation complex of the viral RdRP showed that FPV is capable to make RdRP pause during the reading process, which leads to backtracking (an attempt to recover reading errors), that when repetitive, causes the enzyme to interpret them as a prematurely terminated product, thus stopping the elongation and therefore interrupting the viral replication process(40).FPV has been used successfully against A H1N1 influenza(41,42).…”
mentioning
confidence: 99%